2006
DOI: 10.1088/0029-5515/46/10/001
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen retention of JT-60 open divertor tiles exposed to HH discharges

Abstract: Hydrogen retention in graphite tiles exposed to hydrogen discharges at the JT-60 open divertor has been investigated by means of thermal desorption spectroscopy (TDS). Most of the plasma facing area was covered with re-deposited layers of maximum thickness of about 70 µm appearing at the inner divertor region. Major parts of retained hydrogen were thermally desorbed as hydrogen molecules with a peak temperature of around 970 K. Almost all the hydrogen atoms were retained homogeneously in the re-deposited layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 29 publications
5
23
0
Order By: Relevance
“…Normalized by integrated NBI time (6 Â 10 4 s), this value corresponds to approximately (0.3-1.5) Â 10 18 m À2 s À1 . Although this value is smaller than that of the inner divertor with heavy deposition of carbon [10], the results suggest that the hydrogen isotopes retention in gaps of the whole first wall area could be significantly large.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Normalized by integrated NBI time (6 Â 10 4 s), this value corresponds to approximately (0.3-1.5) Â 10 18 m À2 s À1 . Although this value is smaller than that of the inner divertor with heavy deposition of carbon [10], the results suggest that the hydrogen isotopes retention in gaps of the whole first wall area could be significantly large.…”
Section: Discussionmentioning
confidence: 59%
“…For this reason, it is important to investigate retention behavior of hydrogen isotopes in present tokomaks for prediction of tritium retention in ITER. In tokamaks, hydrogen (H) and deuterium (D) retention and carbon erosion/ deposition in the divertor area has been intensively investigated so far [2][3][4][5][6][7][8][9][10][11][12]. In JT-60U, it was found that the H + D retention in the plasma facing surface and the side surface of the graphite tile in the divertor area is of the order of about 10 22 -10 23 atoms/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The results are compared with previously obtained results for the divertor tiles; both eroded and redeposited ones [2][3][4][5]. Masaki et al [6] have suggested that most of the first wall tiles were eroded and only those inboard tiles a little above the inner baffle plates were deposited.…”
Section: Introductionmentioning
confidence: 80%
“…Previous studies [1][2][3][4][11][12][13][14] have focused on the redeposited layers on divertor tiles and remote areas at rather low temperatures. It has been generally accepted that the first wall is eroded and would retain little hydrogen, compared to hydrogen retention in the redeposited layers on the divertor tiles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, detailed analyses of deuterium and hydrogen in plasma-facing graphite tiles of JT-60U have been performed using secondary ion mass spectroscopy (SIMS), thermal desorption spectroscopy (TDS), nuclear reaction analysis (NRA), elastic recoil detection (ERD) and a scanning electron microscope (SEM) [6][7][8][9][10][11]. Although the SIMS analysis gives depth profiles of hydrogen isotopes together with impurities, it is hard to give quantitative concentrations.…”
Section: Introductionmentioning
confidence: 99%